A National Cross-Sectional Survey of Bullying in Syrian Graduate Medical Education - Swed, Sarya; Shoib, Sheikh; Almoshantaf, Mohammad Bader; Bohsas, Haidara; Hassan, Ahmad Salah Eldin Mohamed; Motawea, Karam R.; Hassan, Noheir Ashraf Ibrahem Fathy; Ahmad, Eman Mohammed Sharif; Sheet, Lana; Khairy, Lina Taha; Bakkour, Agyad; Muwaili, Ali Hadi Hussein; et al. (Frontiers in Public Health, 2022)
Bullying is defined as unpleasant behavior that causes someone to feel disturbed or embarrassed, affecting their self-esteem. Based on this premise, we set out to investigate bullying among Syrian graduate medical education residents and fellows, estimate its prevalence among specific subgroups, and give recommendations to help validate the findings and enhance the graduate medical education training experience. A sample of 278 residents and fellows in Syrian graduate medical school were recruited for the study in a national cross-sectional survey, with 276 participants completing a Bullying survey in 2021 and two people refusing to participate. Participants in the survey were asked to provide basic demographic and programming information and three general Bullying and 20 specific bullying behavior items. Differences across groups were compared for demographic and programmatic stratifications. About 51% of participants had experienced one or more bullying behaviors, 69% said they had been bullied, and 87% said they had witnessed Bullying. Residents and supervisor-attendings were the most common sources of perceived Bullying (~67 and 62%, respectively), followed by patients (58%), nurses (46%), and pharmacists (46%) (33%). More specific bullying behaviors have been recorded by female Arabic Syrians who are shorter than 5'8, have a body mass index (BMI) of 25, and are 30 years old or younger who were -compared to males- more likely to report attempts to minimize and devalue work (55 vs. 34%, P ≤ 0.01) and criticism and work monitoring (56 vs. 33%, P ≤ 0.01). In addition, general medical graduates and PGY-2-PGY-6 respondents reported more specific bullying behaviors than private medical graduates and post-graduate participants in the first year (PGY 1), respectively. For example, a significant difference is noticed when reporting unreasonable pressure to perform work (83 vs. 6%, P ≤ 0.01). Except for physical violence, which does not differ statistically between groups, most bullying behaviors were reported by participants with statistically significant differences between study groups—many residents and fellows in Syria's graduate medical school system report being bullied. Anti-bullying rules and a multidisciplinary strategy including all players in the medical system are essential to eradicating these pervasive practices in healthcare.